The time of Earth's life. (August 2021) - Smith, Cyril
Abstract : In response to David Appell's review of Seven Pillars of Science by John Gribbin (April pp46–47), which discusses the experiments of Stanley Miller and Harold Urey. They created amino acids after just a week by mixing water, ammonia, methane and hydrogen, which suggested that living things are made of the same matter as everything else – and that there is no special "life force"